PENGARUH INOVASI PRODUK DAN NETWORK CAPITAL TERHADAP KINERJA PEMASARAN IKM BATIK PESINDON KOTA PEKALONGAN - Rahma Imaniar Setiasri; Hari Susanta Nugraha (Universitas Diponegoro, 2017)
Marketing performance is a benchmark to know the extent to which the company develops and progresses. To achieve that goal, the Owner of Small and Medium Industry Batik needs to pay attention to the things - things that can affect marketing performance. Moreover, the number of small and medium-sized batik industry in the city of Pekalongan which is a competitor in the batik industry, must demand always innovate and expand the business network. This is what keeps the business going. This study aims to determine the effect of product innovation variables and network capital on marketing performance of IKM Batik Batik Pesindon Pekalongan City. Type of research used is eksplanatory research. The sample used 34 respondents who are the owner of IKM Batik. The sampling technique used is census sampling. Methods of data analysis using correlation test, simple linear regression test, multiple linear regression test, t test and f test with the help of program SPPS (Statistical Product and Service Solutions) version 20.0. The results of the analysis concluded that product innovation and network capital have a positive effect on the marketing performance proven through simple linear regression testing that yield regression value of 0.311 and 0.461. The advice given to the company is to strengthen product innovation and evaluate.